2019
DOI: 10.1007/s13201-019-0892-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the impact of water quality on the infiltration rate of the soil

Abstract: The concept behind of this paper is to check the potential of the three regression-based techniques, i.e. M5P tree, support vector machine (SVM) and Gaussian process (GP), to estimate the infiltration rate of the soil and to compare with two empirical models, i.e. Kostiakov model and multi-linear regression (MLR). Totally, 132 observations were obtained from the laboratory experiments, out of which 92 observations were used for training and residual 40 for testing the models. A double-ring infiltrometer was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…Figure 9 shows result of sensitivity analysis of input parameters. The most sensitive parameters were time (T), water depth (d) (it is in accordance with the results available in literature (Singh et al 2019)) and number of plant (n). The least sensitive parameter was inflow to rain garden (r).…”
Section: Sensitivity Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 9 shows result of sensitivity analysis of input parameters. The most sensitive parameters were time (T), water depth (d) (it is in accordance with the results available in literature (Singh et al 2019)) and number of plant (n). The least sensitive parameter was inflow to rain garden (r).…”
Section: Sensitivity Analysissupporting
confidence: 89%
“…In present study, for GBM and DL the CC values obtained for training and testing data set are 0.999, 0.933 and 0.995, 0.976, respectively. Thus, the accuracy of GBM and DL are much better as compared to other models used by Singh et al (2019).…”
Section: Comparison Of Performancesmentioning
confidence: 93%
See 1 more Smart Citation
“…Some latest studies suggested successful application of soft computing techniques, viz. SVM, GPR, M5 tree and random forest regression to the field of groundwater hydrology (Singh et al 2017(Singh et al , 2019aAngelaki et al 2018;Sihag et al 2018a, b, c;Vand et al 2018;Sihag et al 2019b, c), water resources (Kumar et al 2018;Sepahvand et al 2019;Singh et al 2018a, b;Tiwari and Sihag 2018;Tiwari et al 2019) and engineering (Nain et al 2018(Nain et al , 2019Mehdipour et al 2018;Mohanty et al 2019). Keeping in view the importance of M5 tree and random forest regression techniques, the present research deals with the implementation of these techniques in an attempt to relate unsaturated hydraulic conductivity of the field data measured from 20 locations of Kurukshetra district, Haryana, with the soil physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have developed various conventional models to estimate the IR (Kostiakov, 1932;Philip, 1957;Sihag et al, 2017). Alternatively, the IR can be modelled using soft computing techniques such as the artificial neural network, adaptive neuro-fuzzy inference system, and fuzzy logic system (FLS) approaches (Singh et al, 2018;Singh et al, 2019). The conventional models are site specific and require model parameters, whereas the soft computing-based models are used generally for the study area.…”
Section: Introductionmentioning
confidence: 99%